2000
DOI: 10.1006/mcne.2000.0877
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-Induced Regulation of Netrin Receptors and Modification of Netrin-1 Expression in the Retina of Fish and Grafted Rats

Abstract: To determine whether netrin receptors (DCC, UNC5H1, UNC5H2) and netrin-1 are present in the adult rat retina and may affect regeneration of retinal ganglion cell (RGC) axons into peripheral nerve (PN) grafts, in situ hybridization (ISH) and immunostaining experiments were performed in normal and operated rats. Netrin-1 expression was not found in the optic nerve head of adult rats, normal and postlesion, but appeared transiently at 7 and 14 days after PN grafting. ISH signals of netrin receptors, however, disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 40 publications
0
47
2
Order By: Relevance
“…It is not clear which netrin-1 receptors are expressed by the Xenopus spinal neurons assayed in vitro, and the heterogeneous mixture of cells in these cultures confounds biochemical analyses. RGCs have been shown to express both DCC and multiple Unc5 homologs in zebrafish, rats, and mice (Deiner et al, 1997;Petrausch et al, 2000;Ellezam et al, 2001). Xenopus RGCs express DCC (de la Torre et al, 1997;Shewan et al, 2002), and, although the single identified Xenopus Unc5 homolog is not expressed by RGCs , it seems likely that they express a different family member.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear which netrin-1 receptors are expressed by the Xenopus spinal neurons assayed in vitro, and the heterogeneous mixture of cells in these cultures confounds biochemical analyses. RGCs have been shown to express both DCC and multiple Unc5 homologs in zebrafish, rats, and mice (Deiner et al, 1997;Petrausch et al, 2000;Ellezam et al, 2001). Xenopus RGCs express DCC (de la Torre et al, 1997;Shewan et al, 2002), and, although the single identified Xenopus Unc5 homolog is not expressed by RGCs , it seems likely that they express a different family member.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that pioneering fibers of the optic projection may not be guided by CSs, but that with increasing complexity of the differentiating brain, this cue becomes important for the developing optic projection. The optic projection of fish grows throughout life (Meyer, 1978;Marcus et al, 1999), correlated with the constitutive expression of positive (netrin-1; Petrausch et al, 2000) and negative (ephrin-A2 and -A5; C. G. guidance cues in the adult that are developmentally downregulated in mammals (Wizenmann et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The optic projection of teleost fish, including zebrafish (Marcus et al, 1999), is continuously growing, such that positive (adhesive and attractive) and negative (repellent and inhibitory) guidance molecules that are developmentally downregulated in mammals are still present in the adult fish brain (C. G. Petrausch et al, 2000). These molecules supposedly guide newly growing and regenerating optic axons to their correct targets.…”
mentioning
confidence: 99%
“…To begin to understand whether CALEB might be important for axonal growth in vivo, we analyzed the expression of the putative rat homolog of CALEB, rCALEB/NGC, in the rat retina which serves as a model system to study axon regeneration in the mammalian central nervous system (43,45,49). This system has been frequently used to follow the temporal expression pattern of a number of different mRNAs encoding cell surface proteins implicated in axon growth after ONL (39,46). In rats receiving a sciatic nerve transplant a fraction of RGCs (not more than 5%) are capable of regenerating an axon into the graft.…”
Section: Discussionmentioning
confidence: 99%
“…The described time course for rCALEB/NGC mRNA synthesis after ONL is different from the temporal expression pattern described for other mRNAs examined so far. For example, TAG-1, an axon-associated cell adhesion molecule, as well as the netrin receptors are expressed by adult rat RGCs, but their mRNA is down-regulated and lost after ONL (39,46). Almost all RGCs synthesize L1 mRNA before ONL, and the number of RGCs producing this type of mRNA decreased in parallel with the loss of RGCs due to cell death (39).…”
Section: Discussionmentioning
confidence: 99%